Empagliflozin Protects Cardiac Mitochondrial Fatty Acid Metabolism in a Mouse Model of Diet-Induced Lipid Overload - Makrecka-Kuka, Marina; Korzh, Stanislava; Videja, Melita; Vilks, Karlis; Cirule, Helena; Kuka, Janis; Dambrova, Maija; Liepinsh, Edgars (Cardiovascular drugs and therapy, 2020)
Purpose Sodium-glucose cotransporter 2 (SGLT2) inhibitors prevent heart failure and decrease cardiovascular mortality in patients with type 2 diabetes. Heart failure is associated with detrimental changes in energy metabolism, and the preservation of cardiac mitochondrial function is crucial for the failing heart. However, to date, there are no data to support the hypothesis that treatment with a SGLT2 inhibitor might alter mitochondrial bioenergetics in diabetic failing hearts. Thus, the aim of this study was to investigate the protective effects of empagliflozin on mitochondrial fatty acid metabolism. Methods Mitochondrial dysfunction was induced by 18 weeks of high-fat diet (HFD)-induced lipid overload. Empagliflozin was administered at a dose of 10 mg/kg in a chow for 18 weeks. Palmitate metabolism in vivo, cardiac mitochondrial functionality and biochemical parameters were measured. Results In HFD-fed mice, palmitate uptake was 1.7, 2.3, and 1.9 times lower in the heart, liver, and kidneys, respectively, compared with that of the normal chow control group. Treatment with empagliflozin increased palmitate uptake and decreased the accumulation of metabolites of incomplete fatty acid oxidation in cardiac tissues, but not other tissues, compared with those of the HFD control group. Moreover, empagliflozin treatment resulted in fully restored fatty acid oxidation pathway-dependent respiration in permeabilized cardiac fibers. Treatment with empagliflozin did not affect the biochemical parameters related to hyperglycemia or hyperlipidemia. Conclusion Empagliflozin treatment preserves mitochondrial fatty acid oxidation in the heart under conditions of chronic lipid overload.